Perbedaan Pemberian Air Kelapa Hijau Dan Pijat Effleurage Terhadap Penurunan Dismenore Ringan Pada Remaja Putri Di SMA Citra Nusa Kecamatan Cibinong Kabupaten Bogor : Differences between Giving Green Coconut Water and Effleurage Massage on Reducing Mild Dysmenorrhea in Adolescent Girls at Citra Nusa High School, Cibinong District, Bogor Regency - Rusiyani, Nani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Dysmenorrhea is a disease with the most common physical symptoms that occurs in school-age adolescents with an incidence of around 60-90%. One of the treatments is by giving green coconut water and Massage Effleurage. Based on the results of a preliminary study at Citra Nusa High School, Cibinong District, Bogor Regency, around 30 female students experienced dysmenorrhea.  Methods: The research method was a quasi-experimental design with a pre-test and post-test control group design, a sample size of 30 respondents, technique of purposive sampling. The research instrument used a Visual Analog Scale (VAS) questionnaire. Data is primary data analyzed using Mann-Whitney.  Results: The results of the study mean mild dysmenorrhea given green coconut water before 2,33 and after 0.67, the average mild dysmenorrhea given Massage Effleurage before 2,47 and after 1,13. The results of the bivariate analysis of the differences in giving green coconut water and Massage Effleurage to the reduction of mild dysmenorrhea in young women with a p-value of 0.137.  Discussion: In conclusion, there is no significant difference in the administration of green coconut water and effleurage massage in reducing mild dysmenorrhea in female adolescents. It is expected that students who experience dysmenorrhea before using anti-pain drugs should first use non-pharmacological treatments one of which is green coconut water or Massage Effleurage to reduce pain so they can attend lessons as usual and not reduce concentration.